Focus: Land Law - Webb, Eileen; Stephenson, M. (2015)
Focus: Land Law, 4th edition provides a concise yet comprehensive introduction to the principles of land law in Australia. The book is designed to develop greater understanding of land law by identifying and explaining the key areas of study using a straightforward, structured approach and written in plain English. The authors have attempted to refer to cases and legislation in all states and territories. The book also covers concepts, successive interests, concurrent interests, leases and license, the Torrens system and encumbrances under the Torrens system. Sample problems and guided answers in each chapter are designed to test knowledge by reference to hypothetical scenarios calling for legal analysis.